﻿﻿﻿﻿Sistem Informasi Penentuan Prioritas Pengadaan Obat Menggunakan Metode Analisis Activity Based Costing (ABC) - Nahrun Hartono; Firmansyah Ibrahim; Asminarni Asminarni (Subaltren Inti Media, 2024)
Gisella Farma Pharmacy is a pharmacy that sells a wide variety of medicines. Each type of drug has a different priority level, which causes difficulty in determining priorities for drug procurement. This can lead to a waste of funds and stock buildup, which can be detrimental to the pharmacy. Additionally, in managing drug inventory, regular checks are still required for every request, as there is no real-time information on the amount of drug stock available in the pharmacy. The activity-based costing method is used to assign different priorities to each group of drugs and support drug procurement. Extreme Programming was used in developing this system, with black-box testing as the system testing method. From the results of research using the activity-based costing method: Drug sales data in April showed that 37 items (47.44%) of drugs belonged to class A with a total sales value of 79.54%, 23 items to class B (29.49%) with a total sales value of 15.28%, and 18 items to class C (23.08%) with a total sales value of 5.18%. Drug sales data in May included 31 items (43.06%) of drugs belonging to class A with a total sales value of 79.42%, 21 items to class B (29.17%) with a total sales value of 15.18%, and 20 items to class C (27.78%) with a total sales value of 5.40%. Drug sales data in June showed that 39 items (49.86%) of drugs belonged to class A with a total sales value of 79.42%, 27 items to class B (29.67%) with a total sales value of 15.37%, and 25 items to class C (27.47%) with a total sales value of 5.21%. Drug sales data in July included 40 items (44.94%) of drugs belonging to class A with a total sales value of 79.74%, 24 items to class B (26.97%) with a total sales value of 14.96%, and 25 items to class C (28.09%) with a total sales value of 5.30%.